Evaluation of wood coating performance and volatile organic compounds - Genc, Umut; Koc, Kucuk Huseyin (Maderas. Ciencia y Tecnología, 2024)
The aim of this study was to evaluate the environment-performance relationship of surface coating applications on data obtained by measuring the emission rates of volatile organic compounds in polyurethane and water-based varnishes. For this purpose, polyurethane and water-based varnishes from five different companies were applied to the test samples of Entandrophragma cylindricum (sapele) and Piptadeniastrum africanum (dabema), both widely used in the production of urban furniture. Volatile organic compound, hardness and adhesion strength were measured during application. When evaluated in terms of performance, polyurethane varnishes showed superior hardness, while water-based varnishes demonstrated better adhesion after the UV test. The hardness values of polyurethane varnishes before and after the UV aging test were 15,9 s and 79,403 s, respectively, while forwater-based varnishes were , the values were 114,92 s and 75,406 s. The adhesion values of water-based varnishes were 2,885 MPa and 1,18 MPa before and after the UV aging test, and for polyurethane varnishes 3,13 MPa and 1,05 MPa for. When the environment-oriented results were evaluated, the ; emission values of volatile organic compounds in polyurethane varnish applications were found to be significantly higher than those in in water-based varnishes applications. While the total emission rate of volatile organic compounds detected in polyurethane varnishes was 53,63 mg/Nm3, while only one brand of water-based varnishes showed a measurable emission value, recorded at 0,0057 mg/Nm3. The volatile organic compounds emission values of other water-based varnishes were below the device detection limit (<0,0035 mg/Nm3), and therefore could not be measured.